The Cinema of Mika Kaurismäki Transvergent Cinescapes, Emergent Identities - Kääpä, Pietari (Intellect, 2011)
Mika Kaurismäki's films challenge many boundaries - national societies, genre formations, art/popular culture, fiction/documentary, humanity/nature and problematic distinctions between different zones of development. Synthesizing concepts from a range of thematic frameworks - e.g. auteurism, eco-philosophy, genre, cartography, cineaste networks, global reception, distribution and exhibition practices, and the potential of postnationalism - this book provides an interdisciplinary reading of Kaurismäki's cinema. The notion of 'transvergence' - of thinking in heterogeneous and polyphonal terms - emerges as an analytical method for exploring the power of these films. Through this, the volume encourages rethinking transnational cinema studies in relation to many oft-debated notions such as Finnish culture, European identity, cosmopolitanism and globalization.